The Boston Fed study of consumer behavior and payment choice: A survey of Federal Reserve System employees - Marques Benton; Krista Blair; Marianne Crowe; Scott Schuh (Federal Reserve Bank of Boston, 2007)
The way people pay for goods and services is changing dramatically, but little data and research on consumer behavior and payment choice are publicly available. This paper describes the results of a survey of payment behavior and attitudes taken by Federal Reserve employees in 2004. Major contributions of the survey are that it asks: 1) why payment choices are made; 2) why individual payment behavior has changed; and 3) why individual-specific payment characteristics matter for payment choice. Although the survey is not statistically representative of U.S. consumers, and thus may not provide accurate estimates of aggregate U.S. payment trends, many results are consistent with data from more representative payment surveys. For example, the data show a trend away from check-writing and toward electronic and emerging payment methods, but the choice of payment method depends on the type of payment, amount of payment, and other complex factors. Also, cost, convenience, and control over timing are the most important characteristics determining respondents' adoption and use of payment methods. We find that payment characteristics vary widely across respondents, partly because of inherent heterogeneity but perhaps also because of measurement error, misperception, or inadequate information (lack of consumer education). Cross-sectional evidence shows that respondents tend to use payment methods in a manner broadly consistent with their reported assessents of the payment characteristics.
Keywords: D12; D14; E41; C81; 330; Zahlungsverkehr; Bargeldloser Zahlungsverkehr; Konsumentenverhalten; USA